Copper multi-channel connected self-reduction TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst as well as preparation method and application of copper multi-channel connected self-reduction TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst

By using the self-reducing TiO2/CuIn bimetaloporphyrin MOFs structure connected by copper multi-channel in the photocatalyst, CuCl2 is reduced to Cu2O by using the self-reduction effect of the TiO2 precursor, and a multi-channel connection is constructed, which solves the problem that existing photocatalysts cannot effectively retain the reducing side chain and reduce high-valent metal ions under the conditions of no added reducing agent, and achieves efficient photocatalytic hydrogen production activity.

CN119680643APending Publication Date: 2025-03-25SHANGHAI INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411618548.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing photocatalysts cannot effectively retain the reducing side chain organic groups of the TiO2 precursor during the photocatalytic hydrogen production process, and cannot reduce high-valent metal ions to higher-active low-valent metal ions without the addition of a reducing agent.

Method used

The self-reducing TiO2/CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channel is used to mix the TiO2 precursor with CuIn porphyrin MOFs and CuCl2 through solvothermal reaction, and CuCl2 is reduced to CuCl2 by using the self-reduction of the TiO2 precursor to build a multi-channel connection to improve photocatalytic activity.

Benefits of technology

It is possible to reduce high-valent metal ions to lower-valent metal ions with higher activity without additive reducing agent, which enhances the photocatalytic activity of the photocatalyst and is simple in the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680643A_ABST
    Figure CN119680643A_ABST
Patent Text Reader

Abstract

The invention relates to a copper multi-channel connected self-reduction TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst as well as a preparation method and application of the copper multi-channel connected self-reduction TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst. CuCl2, a TiO2 precursor with reduction activity and CuIn bimetallic porphyrin MOFs with a plurality of metal binding sites and reaction activity centers are subjected to solvothermal reaction, Cu < 2 + > is partially reduced into Cu < + > with higher photocatalytic activity by utilizing the reducibility of the TiO2 precursor, and multi-channel connection is established between TiO2 and the CuIn bimetallic porphyrin MOFs, so that the photocatalytic activity of the CuIn bimetallic porphyrin MOFs is improved, and the photocatalytic activity of the CuIn bimetallic porphyrin MOFs is improved. Therefore, a series of photocatalysts with efficient photocatalytic hydrogen production activity are obtained. Compared with the prior art, the self-reduction TiO2 / CuIn double-metal porphyrin MOFs photocatalyst prepared by the method has the advantages that valence state transformation is completed by utilizing the oxidation-reduction activity of the components without additionally adding a reducing agent, so that the self-reduction TiO2 / CuIn double-metal porphyrin MOFs photocatalyst is simpler, greener and relatively lower in cost, multi-channel connection is established between TiO2 and CuIn double-metal porphyrin MOFs by multi-valence copper, and the self-reduction TiO2 / CuIn double-metal porphyrin MOFs photocatalyst is more environment-friendly. The interface resistance is obviously reduced, and the charge separation efficiency and the photocatalytic activity are higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels, and a preparation method and application thereof. Background Art

[0002] With the overuse of fossil energy, global warming, natural disasters, severe weather and other issues have been caused. The development of more and more sustainable and renewable energy systems has attracted people's attention. Hydrogen energy and solar energy are the cleanest green energy sources. Therefore, photocatalytic hydrogen production technology has made significant progress since Fujishima and Honda discovered that titanium dioxide can decompose water to produce hydrogen under ultraviolet light in 1972. In the past few decades, various semiconductor materials have been used in photocatalytic hydrogen production, including g-C3N4, CdIn2S4, metal organic frameworks (MOFs), etc. Porphyrin-based MOFs have high porosity, multiple metal active sites, superior visible light response ability and flexible and adjustable network structure, showing remarkable characteristics in the field of photocatalysis.

[0003] Titanium dioxide (TiO2) has attracted extensive attention due to its low cost, high catalytic activity, strong chemical stability, strong solid antioxidant capacity, non-toxicity, and safety. TiO2 has a wide band gap (3.2eV) and can only be excited by ultraviolet radiation. In order to overcome this problem, porphyrin compounds are used as sensitizers to broaden the absorption range of the TiO2 spectrum, while constructing metal ion channels to accelerate the transfer of electron holes in TiO2 and improve its photocatalytic activity.

[0004] Patent publication number CN115487799A discloses a strontium lithium titanate / titanium dioxide heterojunction photocatalyst and its preparation method and application. After in-situ hydrolysis of tetrabutyl titanate (TBOT) on carbon (C) balls, strontium source and lithium source are added for high-temperature calcination, which is used for photocatalytic hydrogen production. High-temperature calcination destroys the reducing side chain groups generated by the in-situ hydrolysis process of TBOT. Patent publication number CN118403632A discloses a copper ion-doped and copper-loaded Cu-TiO2 / Cu for photocatalytic hydrogen production. Copper-doped TiO2 can improve the spectral response of TiO2, but it also anchors the metal active sites of copper (Cu), and the metal active centers and active sites are relatively few. Patent publication number CN115090330A discloses a method for preparing SNP-TiO2@Cu-MOF composite material photocatalyst and its application, using cupric chloride dihydrate (CuCl2·2H2O) as the precursor of Cu-MOF, and preparing SNP-TiO2@Cu-MOF photocatalyst by hydrothermal synthesis. The TiO2 prepared by the solvothermal method in this patent has no reducing effect, and a variety of organic solvents are used in the process of preparing hybrid materials. The TiO2 prepared by the solvothermal method in this patent has no reducing effect, and a variety of organic solvents are used in the process of preparing hybrid materials. The above methods all have certain improvements on TiO2 in photocatalysis, but they cannot retain the reducing side chain organic groups of the self-reducing TiO2 precursor, and they cannot use the material's own reducing effect to reduce high-valent metal ions to more active low-valent metal ions without adding any reducing agent. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a copper multi-channel connected self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst and its preparation method and application. The present invention uses the self-reduction effect of the TiO2 precursor to self-reduce high-valent metal ions to more active low-valent metal ions during the hybridization process. At the same time, there is no need to add any reducing agent. Only the characteristics of the material itself are used to enhance the photocatalytic activity of the hybrid material. It has the advantages of a simple catalyst synthesis process and excellent photocatalytic activity.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connections. Through a one-pot method, a first copper salt, a TiO2 precursor, and a CuIn porphyrin MOFs are mixed in a first organic solvent, and a solvothermal reaction is performed to obtain a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connections, and the reaction is completed.

[0008] Furthermore, the mass ratio of the first copper salt, the TiO2 precursor, and the CuIn porphyrin MOFs is 0.5 to 16:100:4, preferably 4 to 16:100:4, and more preferably 8:100:4;

[0009] The mass volume ratio of the TiO2 precursor to the first organic solvent is 50:3-5 mg / mL, preferably 50:4 mg / mL.

[0010] Furthermore, the temperature of the solvent thermal reaction is 100-140° C., and the reaction time is 20-30 hours.

[0011] Further, the first copper salt is copper chloride (CuCl2);

[0012] The first organic solvent is dimethylformamide (DMF).

[0013] Furthermore, after the solvothermal reaction, centrifugation, washing and drying are performed to obtain a self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels.

[0014] Furthermore, the preparation process of the TiO2 precursor is: tetrabutyl titanate, a hydrolysis inhibitor, water, and nitric acid are mixed by a sol-gel method, and the TiO2 precursor is obtained by heating, stirring, drying, and grinding.

[0015] Furthermore, the volume ratio of tetrabutyl titanate, hydrolysis inhibitor, water and nitric acid is 5-15:5-10:100-200:1, preferably 8-12:5-8:120-170:1, and more preferably 10:6:150:1;

[0016] The hydrolysis inhibitor includes one or more of ethanol, acetone, and acetylacetone;

[0017] The heating and stirring temperature is 40 to 80°C and the time is 5 to 10 hours;

[0018] The drying temperature is 120-180°C.

[0019] Furthermore, the hydrolysis inhibitor comprises a mixture of ethanol, acetone and acetylacetone in a volume ratio of 1:(0.5-2):(0.5-2), preferably 1:1:1.

[0020] Furthermore, the preparation process of the CuIn bimetallic porphyrin MOFs is: tetrakis(4-carboxyphenyl)porphine (TCPP), benzoic acid, a second copper salt, and an indium salt are mixed in a second organic solvent, heated to reflux, cooled, centrifuged, and dried to obtain CuIn porphyrin MOFs.

[0021] Furthermore, the mass ratio of TCPP, benzoic acid, the second copper salt, and the indium salt is 2-8:1-5:5-15:10, preferably 2-6:2-3:7.5-12.5:10, and more preferably 4:2.5:10:10;

[0022] The second copper salt is CuCl2;

[0023] The indium salt is In(NO3)3;

[0024] The second organic solvent is DMF;

[0025] The mass volume ratio of the TCPP to the second organic solvent is 20-80:100 mg / mL, preferably 30-50:100 mg / mL;

[0026] The heating reflux temperature is 120-180°C and the time is 0.5-5h;

[0027] The drying temperature is 40-80°C.

[0028] The second technical solution of the present invention is to provide a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels, which is prepared by the above-mentioned preparation method.

[0029] The self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels was analyzed by SEM and TEM. It was found that the TiO2 precursor was a block structure, and the CuIn bimetallic porphyrin MOFs was a sheet structure loaded on the TiO2 precursor. TEM showed that the block TiO2 precursor was connected by many small TiO2 particles, indicating that the TiO2 block structure was due to the side chain reducing organic groups connecting the TiO2 small particles, causing the TiO2 small particles to accumulate into a block TiO2 precursor. It also shows that there are side chain reducing organic groups in the TiO2 precursor.

[0030] The third technical solution of the present invention is to provide a copper multi-channel connected self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst for application in the field of photocatalysis, wherein the copper multi-channel connected self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst is used as a photocatalyst for hydrolysis and hydrogen production.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] (1) The present invention does not adopt high-temperature calcination of TiO2 precursor, but prepares sol TiO2 by a more gentle sol-gel method and then heat-treats and dries it, thereby retaining the reducing side chain organic groups to obtain a reducing TiO2 precursor. The TiO2 precursor itself has the reducing property, and after participating in the solvothermal reaction, the divalent copper ions in CuCl2 and CuIn bimetallic porphyrin MOFs are reduced to monovalent copper ions, thereby making the copper in the hybrid material channel and the metal sites in CuIn porphyrin MOFs more active.

[0033] (2) The present invention adds CuCl2 to TiO2 / CuIn bimetallic porphyrin MOFs through a simple one-pot method. CuCl2 is reduced to Cu2O on the surface of the hybrid material. Inside the hybrid material, the various valence states of copper ions in CuCl2 construct channels in the TiO2 precursor and the CuIn bimetallic porphyrin MOFs. On the one hand, the low-valent copper ions act as co-catalysts in the photocatalytic reaction. On the other hand, the low-valent copper ions can promote the separation and transfer of electrons and holes in the photocatalytic reaction. In addition, the entire reaction process does not require the addition of any reducing agent, and only utilizes the reduction effect of the reducing TiO2 precursor obtained by heat treatment and drying after TiO2 is prepared by the sol-gel method.

[0034] (3) The present invention obtains bimetallic CuIn porphyrin MOFs by reacting TCPP, benzoic acid, copper salt and indium salt. Multiple porphyrin molecules are orderly arranged in the ordered two-dimensional structure of CuIn bimetallic porphyrin MOFs. After solvothermal reaction with TiO2 precursor, they can serve as a light absorption and electron transfer network to improve the light absorption and electron transfer of TiO2. The bimetallic CuIn porphyrin MOFs have more abundant metal binding sites and reaction active centers, which are beneficial to the separation of electron-hole pairs and the improvement of photocatalytic reaction activity.

[0035] (4) In order to improve the photocatalytic activity of TiO2 nanoparticles, the present invention reduces CuCl2 to Cu2O on the surface of TiO2 / CuIn bimetallic porphyrin MOFs through a solvothermal reaction and utilizes the self-reduction of the TiO2 precursor. At the same time, the various valence states of the copper ions in CuCl2 exist in the TiO2 / CuIn bimetallic porphyrin MOFs in a multi-channel form. The multi-channel connection established between the multivalent copper and the CuIn bimetallic porphyrin MOFs exposes more metal active centers and active sites of Cu. +On the one hand, it provides the role of a co-catalyst, and on the other hand, it also acts as an electron transfer bridge in the construction of TiO2 and CuIn bimetallic porphyrin MOFs inside the hybrid material. After CuIn bimetallic porphyrin MOFs are composited with TiO2, the light response region of TiO2 will be broadened. At the same time, the reducibility of the self-reducing TiO2 precursor will also reduce the copper ions in the CuIn bimetallic porphyrin MOFs. In the solvothermal reaction, the TiO2 precursor and CuIn bimetallic porphyrin MOFs complement and promote each other. In addition, the bimetallic CuIn porphyrin MOFs have more abundant metal binding sites and reaction active centers, which are conducive to the separation of electron-hole pairs. In the ordered two-dimensional structure of CuIn bimetallic porphyrin MOFs, multiple porphyrin molecules are arranged in an orderly manner, which can serve as a light absorption and electron transfer network to improve the light absorption and electron transfer of TiO2. Therefore, in order to overcome the existing defects of TiO2, the present invention introduces CuIn porphyrin MOFs with high efficiency light absorption and fast electron transfer on the TiO2 precursor, and constructs channels in the TiO2 precursor and CuIn bimetallic porphyrin MOFs after adding Cu ions to prepare organic-inorganic heterogeneous photocatalysts. Among the methods for improving the photocatalytic activity of TiO2, constructing a semiconductor composite heterostructure is a very promising method.

[0036] (5) The present invention uses a self-reducing TiO2 precursor as the main body and composites CuIn bimetallic porphyrin MOFs to improve the spectral response of TiO2. After adding copper, it exists in a multi-channel form to promote the progress of the photocatalytic reaction. The metal ion content is low and the amount used is small. The preparation process of the photocatalytic material is simple and economical, and the photocatalytic hydrogen production activity is excellent.

[0037] (6) The present invention prepares a TiO2 precursor having a reducing organic group on the side chain, and only a small amount of DMF is used as a reaction solvent in the process of hybridizing CuIn bimetallic porphyrin MOFs. The CuIn bimetallic porphyrin MOFs are self-reduced during the hybridization process. 2+ Reduction to Cu + , Cu + It can accelerate the process of photocatalytic reaction. In addition, multiple porphyrin molecules are arranged in an orderly manner in the ordered two-dimensional structure of bimetallic CuIn porphyrin MOFs, which can serve as a light absorption and electron transfer network to improve the light absorption and electron transfer of TiO2, which is beneficial to improve the photocatalytic hydrogen production activity of the composite photocatalyst. In this work, the high-valent metal ions are reduced to more active low-valent metal ions by the reduction effect of the material itself without adding any reducing agent. At the same time, Cu constructs multivalent channels in TiO2 / CuIn bimetallic porphyrin MOFs to accelerate electron transfer in the hybrid material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1This is a SEM image of the self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels as shown in Example 1;

[0039] Figure 2 TEM image of the self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels as shown in Example 1;

[0040] Figure 3 The photocatalytic hydrogen production rate of the self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels in Example 1 in TEOA solution for 5 consecutive times;

[0041] Figure 4 The self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalysts connected by copper multi-channels shown in Examples 1 to 5 are compared in terms of hydrogen production activity when different contents of the first copper source are added;

[0042] Figure 5 The hydrogen production activity comparison of the self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels of Example 1, the TiO2 / CuIn porphyrin MOFs photocatalyst of Comparative Example 1, and the TiO2 precursor of Comparative Example 2;

[0043] Figure 6 The hydrogen production activity comparison of the self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels of Example 1, the TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels of Comparative Example 3, and the TiO2 / CuIn bimetallic porphyrin MOFs (H2O) photocatalyst connected by copper multi-channels of Comparative Example 4;

[0044] Figure 7 The hydrogen production activity of the self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels of Example 1 is compared with that of the fixed copper site TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 5;

[0045] Figure 8 This is a comparison of the hydrogen production activity of the self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 1 and the self-reduced TiO2 / CuAl bimetallic porphyrin MOFs photocatalyst of Comparative Example 6. DETAILED DESCRIPTION

[0046] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0047] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.

[0048] In the following examples, all the following chemicals were used as received without further purification. The CAS number of TCPP is 14609-54-2, the brand is Frontier Scientific, purchased from Anolen (Beijing) Biotechnology Co., Ltd.; the CAS number of DMF is 68-12-2, the brand is Adamas, purchased from Shanghai Titan Technology Co., Ltd.; the CAS number of tetrabutyl titanate is 5593-70-4, the brand is Greagent, purchased from Shanghai Titan Technology Co., Ltd.; the CAS number of CuCl2·2H2O is 10125-13-0, the brand is Adamas, purchased from Shanghai Titan Technology Co., Ltd.; the CAS number of In(NO3)3 is 13770-61-1, the brand is Adamas, purchased from Shanghai Titan Technology Co., Ltd.

[0049] Example 1

[0050] A self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels, the preparation method of which comprises the following steps:

[0051] (I) Preparation of TiO2 precursor

[0052] Add 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) to 75 mL of deionized water, and add 0.5 mL of nitric acid. Heat and stir in a water bath at 60°C for 7 h to obtain a sol, dry at 150°C, cool to room temperature, and then grind to obtain a TiO2 precursor.

[0053] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0054] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0055] (III) Preparation of self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalysts with copper multi-channel connections

[0056] In a 25 mL round-bottom flask, 8 mg of CuCl2·2H2O, 100 mg of TiO2 precursor, 4 mg of CuIn porphyrin MOFs, and 8 mL of DMF were added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and solvothermally reacted at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels.

[0057] (IV) Photocatalytic hydrogen production experiment

[0058] The method is as follows: 10 mg of copper multi-channel connected self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst was dispersed in 10 mL of deionized water, and after ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine were added to the catalyst. After that, the sample was stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas was taken every 1 hour, and the hydrogen production was measured by gas chromatography.

[0059] Example 2

[0060] A self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels is mostly the same as Example 1, except that different amounts of CuCl2·2H2O are added in step (iii). The preparation method thereof comprises the following steps:

[0061] (I) Preparation of TiO2 precursor

[0062] Add 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) to 75 mL of deionized water, and add 0.5 mL of nitric acid. Heat and stir in a water bath at 60°C for 7 h to obtain a sol, dry at 150°C, cool to room temperature, and then grind to obtain a TiO2 precursor.

[0063] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0064] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0065] (III) Preparation of self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalysts with copper multi-channel connections

[0066] In a 25 mL round-bottom flask, 0.5 mg of CuCl2·2H2O, 100 mg of TiO2 precursor, 4 mg of CuIn porphyrin MOFs, and 8 mL of DMF were added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels.

[0067] (IV) Photocatalytic hydrogen production experiment

[0068] The method is as follows: 10 mg of copper multi-channel connected self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst was dispersed in 10 mL of deionized water, and after ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine were added to the catalyst. After that, the sample was stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas was taken every 1 hour, and the hydrogen production was measured by gas chromatography.

[0069] Example 3

[0070] A self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels is mostly the same as Example 1, except that different amounts of CuCl2·2H2O are added in step (iii). The preparation method thereof comprises the following steps:

[0071] (I) Preparation of TiO2 precursor

[0072] Add 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) to 75 mL of deionized water, and add 0.5 mL of nitric acid. Heat and stir in a water bath at 60°C for 7 h to obtain a sol, dry at 150°C, cool to room temperature, and then grind to obtain a TiO2 precursor.

[0073] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0074] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0075] (III) Preparation of self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalysts with copper multi-channel connections

[0076] In a 25 mL round-bottom flask, 2 mg of CuCl2·2H2O, 100 mg of TiO2 precursor, 4 mg of CuIn porphyrin MOFs, and 8 mL of DMF were added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels.

[0077] (IV) Photocatalytic hydrogen production experiment

[0078] The method is as follows: 10 mg of copper multi-channel connected self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst was dispersed in 10 mL of deionized water, and after ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine were added to the catalyst. After that, the sample was stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas was taken every 1 hour, and the hydrogen production was measured by gas chromatography.

[0079] Example 4

[0080] A self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels is mostly the same as Example 1, except that different amounts of CuCl2·2H2O are added in step (iii). The preparation method thereof comprises the following steps:

[0081] (I) Preparation of TiO2 precursor

[0082] Add 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) to 75 mL of deionized water, and add 0.5 mL of nitric acid. Heat and stir in a water bath at 60°C for 7 h to obtain a sol, dry at 150°C, cool to room temperature, and then grind to obtain a TiO2 precursor.

[0083] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0084] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0085] (III) Preparation of self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalysts with copper multi-channel connections

[0086] In a 25 mL round-bottom flask, 4 mg of CuCl2·2H2O, 100 mg of TiO2 precursor, 4 mg of CuIn porphyrin MOFs, and 8 mL of DMF were added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and solvothermally reacted at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels.

[0087] (IV) Photocatalytic hydrogen production experiment

[0088] The method is as follows: 10 mg of copper multi-channel connected self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst was dispersed in 10 mL of deionized water, and after ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine were added to the catalyst. After that, the sample was stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas was taken every 1 hour, and the hydrogen production was measured by gas chromatography.

[0089] Example 5

[0090] A self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels is mostly the same as Example 1, except that different amounts of CuCl2·2H2O are added in step (iii). The preparation method thereof comprises the following steps:

[0091] (I) Preparation of TiO2 precursor

[0092] Add 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) to 75 mL of deionized water, and add 0.5 mL of nitric acid. Heat and stir in a water bath at 60°C for 7 h to obtain a sol, dry at 150°C, cool to room temperature, and then grind to obtain a TiO2 precursor.

[0093] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0094] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0095] (III) Preparation of self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalysts with copper multi-channel connections

[0096] In a 25 mL round-bottom flask, 16 mg of CuCl2·2H2O, 100 mg of TiO2 precursor, 4 mg of CuIn porphyrin MOFs, and 8 mL of DMF were added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels.

[0097] (IV) Photocatalytic hydrogen production experiment

[0098] The method is as follows: 10 mg of copper multi-channel connected self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst was dispersed in 10 mL of deionized water, and after ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine were added to the catalyst. After that, the sample was stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas was taken every 1 hour, and the hydrogen production was measured by gas chromatography.

[0099] Comparative Example 1

[0100] A self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst, which is mostly the same as Example 1, except that CuCl2·2H2O is not added in step (iii), and its preparation method comprises the following steps:

[0101] (I) Preparation of TiO2 precursor

[0102] Add 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) to 75 mL of deionized water, and add 0.5 mL of nitric acid. Heat and stir in a water bath at 60°C for 7 h to obtain a sol, dry at 150°C, cool to room temperature, and then grind to obtain a TiO2 precursor.

[0103] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0104] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0105] (III) Preparation of TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst

[0106] In a 25 mL round-bottom flask, 100 mg of TiO2 precursor, 4 mg of CuIn porphyrin MOFs, and 8 mL of DMF were added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst.

[0107] (IV) Photocatalytic hydrogen production experiment

[0108] The method is as follows: 10 mg of self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst was dispersed in 10 mL of deionized water, and after ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine were added to the catalyst. After that, the sample was stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas was taken every 1 hour, and the hydrogen production was measured by gas chromatography.

[0109] Comparative Example 2

[0110] A TiO2 precursor photocatalyst, the preparation method of which comprises the following steps:

[0111] (I) Preparation of TiO2 precursor

[0112] 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) were added to 75 mL of deionized water, and 0.5 mL of nitric acid was added, and heated in a water bath at 60°C with stirring for 7 h. The TiO2 sol was then dried at 150°C, cooled to room temperature, and ground to obtain a TiO2 precursor.

[0113] (II) Photocatalytic hydrogen production experiment

[0114] The method is as follows: 10 mg of TiO2 precursor is dispersed in 10 mL of deionized water. After 10 minutes of ultrasonication, 40 mL of deionized water and 10 mL of triethanolamine are added to the catalyst. After that, the sample is stored under a 300 W Xe lamp (the spectral range of the lamp is 340 nm-780 nm) for analysis of photocatalytic performance. 1 mL of gas is taken every 1 hour, and the amount of hydrogen produced is measured by gas chromatography.

[0115] Comparative Example 3

[0116] A copper multi-channel connected TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst, which is mostly the same as Example 1, except for step (1), and its preparation method includes the following steps:

[0117] (I) Preparation of TiO2 nanoparticles

[0118] 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) were added to 75 mL of deionized water, and 0.5 mL of nitric acid was added, and heated in a water bath at 60°C with stirring for 7 h. The TiO2 sol was then dried at 150°C, cooled to room temperature, ground, and calcined in a muffle furnace at 350°C for 2 h to obtain TiO2 nanoparticles.

[0119] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0120] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0121] (III) Preparation of Copper Multichannel TiO2 / CuIn Bimetallic Porphyrin MOFs Photocatalyst

[0122] 8 mg of CuCl2·2H2O, 100 mg of TiO2 nanoparticles, 4 mg of CuIn porphyrin MOFs were added to a 25 mL round-bottom flask, and 8 mL of DMF was added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and solvothermally reacted at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a copper multi-channel TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst.

[0123] (IV) Photocatalytic hydrogen production experiment

[0124] The method is as follows: 10 mg of copper multi-channel TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst is dispersed in 10 mL of deionized water. After ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine are added to the catalyst. After that, the sample is stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas is taken every 1 hour, and the amount of hydrogen produced is measured by gas chromatography.

[0125] Comparative Example 4

[0126] A copper multi-channel self-reducing TiO2 / CuIn porphyrin MOFs (H2O) photocatalyst, which is mostly the same as Example 1, except that DMF is replaced by H2O in step (iii), and its preparation method comprises the following steps:

[0127] (I) Preparation of TiO2 precursor

[0128] 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) were added to 75 mL of deionized water, and 0.5 mL of nitric acid was added, and heated in a water bath at 60°C with stirring for 7 h. The TiO2 sol was then dried at 150°C, cooled to room temperature, and ground to obtain a TiO2 precursor.

[0129] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0130] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0131] (III) Preparation of Copper Multichannel Self-reduced TiO2 / CuIn Bimetallic Porphyrin MOFs Photocatalyst

[0132] 8 mg of CuCl2·2H2O, 100 mg of TiO2 nanoparticles, 4 mg of CuIn porphyrin MOFs were added to a 25 mL round-bottom flask, and 8 mL of H2O was added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and hydrothermally reacted at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a copper multi-channel self-reduced TiO2 / CuIn bimetallic porphyrin MOFs (H2O) photocatalyst.

[0133] (IV) Photocatalytic hydrogen production experiment

[0134] The method is as follows: 10 mg of copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs (H2O) photocatalyst is dispersed in 10 mL of deionized water. After ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine are added to the catalyst. After that, the sample is stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas is taken every 1 hour, and the amount of hydrogen produced is measured by gas chromatography.

[0135] Comparative Example 5

[0136] The copper-site-fixed TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst is mostly the same as that in Example 1, except for the differences in steps (i) and (iii). The preparation method thereof comprises the following steps:

[0137] (I) Cu-TiO2 nanoparticles

[0138] 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) were added to 75 mL of deionized water, and 0.5 mL of nitric acid was added, and heated in a water bath at 60°C and stirred for 7 h. Then 105 mg of CuCl2·2H2O was added and stirred at room temperature for 12 h, and then the Cu-TiO2 sol was dried at 150°C, cooled to room temperature, and ground to obtain Cu-TiO2 nanoparticles.

[0139] (II) Preparation of CuIn bimetallic porphyrin MOFs

[0140] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and In(NO3)3·3H2O (0.1 g, 0.28 mmol) were dissolved in 100 mL DMF and heated to reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0141] (III) Preparation of TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with fixed copper sites

[0142] 100 mg of Cu-TiO2 nanoparticles, 4 mg of CuIn porphyrin MOFs, and 8 mL of DMF were added to a 25 mL round-bottom flask, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 24 h. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with fixed copper sites.

[0143] (IV) Photocatalytic hydrogen production experiment

[0144] The method is as follows: 10 mg of fixed copper site TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst was dispersed in 10 mL of deionized water, and after ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine were added to the catalyst. After that, the sample was stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas was taken every 1 hour, and the hydrogen production was measured by gas chromatography.

[0145] Comparative Example 6

[0146] A self-reducing TiO2 / CuAl bimetallic porphyrin MOFs photocatalyst is similar to Example 1 in most aspects except for the differences in steps (ii) and (iii). The preparation method thereof comprises the following steps:

[0147] (I) Preparation of TiO2 precursor

[0148] 5 mL of tetrabutyl titanate and 3 mL of hydrolysis inhibitor (1 mL each of ethanol, acetone, and acetylacetone) were added to 75 mL of deionized water, and 0.5 mL of nitric acid was added, and heated in a water bath at 60°C with stirring for 7 h. The TiO2 sol was then dried at 150°C, cooled to room temperature, and ground to obtain a TiO2 precursor.

[0149] (II) Preparation of CuAl bimetallic porphyrin MOFs

[0150] TCPP (0.04 g, 0.06 mmol), benzoic acid (0.025 g, 0.2 mmol), CuCl2·2H2O (0.1 g, 0.58 mmol) and Al(NO3)3·9H2O (0.1 g, 0.27 mmol) were dissolved in 100 mL DMF and heated under reflux at 150 °C. The mixture was cooled to room temperature to obtain a pink solution, which was washed with ethanol and centrifuged until the filtrate was clear. The pink solid was dried under vacuum at 60 °C to obtain CuIn bimetallic porphyrin MOFs.

[0151] (III) Preparation of TiO2 / CuAl bimetallic porphyrin MOFs photocatalyst

[0152] In a 25 mL round-bottom flask, 100 mg of TiO2 precursor, 4 mg of CuAl bimetallic porphyrin MOFs, and 8 mL of DMF were added, stirred for 2 h, and the mixed solution was transferred to a 10 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 24 hours. Finally, centrifuged at 7500 rpm, washed three times with ethanol, and vacuum dried at 60 ° C to obtain a self-reduced TiO2 / CuAl bimetallic porphyrin MOFs photocatalyst.

[0153] (IV) Photocatalytic hydrogen production experiment

[0154] The method is as follows: 10 mg of self-reducing TiO2 / CuInAl bimetallic porphyrin MOFs photocatalyst was dispersed in 10 mL of deionized water, and after ultrasonication for 10 minutes, 40 mL of deionized water and 10 mL of triethanolamine were added to the catalyst. After that, the sample was stored under a 300W Xe lamp (the spectral range of the lamp is 340nm-780nm) for analyzing the photocatalytic performance. 1 mL of gas was taken every 1 hour, and the hydrogen production was measured by gas chromatography.

[0155] The photocatalysts prepared in Comparative Examples 1 to 5 and Comparative Examples 1 to 6 were characterized and tested.

[0156] like Figure 1The SEM image of the copper multi-channel self-reducing TiO2 / CuIn porphyrin MOFs photocatalyst shown in Example 1 is shown in FIG. Figure 1 It can be seen that the main material TiO2 precursor is a block structure, and flake CuIn bimetallic porphyrin MOFs can be found on the surface of TiO2. At the same time, the addition of Cu makes the surface of the TiO2 precursor smoother.

[0157] like Figure 2 The TEM image of the copper multi-channel self-reduced TiO2 / CuIn porphyrin MOFs photocatalyst of Example 1 is shown. Figure 2 It can be seen that TEM shows the accumulation of smaller TiO2 nanoparticles. The block structure of the TiO2 precursor is due to the connecting effect of the reducing organic groups on the side chains of the smaller TiO2 nanoparticles, which leads to the accumulation of block structures.

[0158] Figure 3 Shown is a comparison of the hydrogen production activity of the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Example 1 and Examples 2, 3, 4, and 5 under different contents of the first copper source. It can be found that with the increase of the content of the first copper source, the hydrogen production activity of the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst shows a trend of first increasing and then decreasing. It can be concluded that the optimal ratio is when 8 mg of the first copper source is added, which has the optimal hydrogen production activity.

[0159] Figure 4 The photocatalytic hydrogen production rate of the copper multi-channel self-reducing TiO2 / CuIn porphyrin MOFs photocatalyst of Example 1 in 50ml water and 10ml TEOA solution is shown for 5 consecutive times, which is used to evaluate the applicability of the catalyst in large-scale production. To this end, the nanocomposite catalyst was used in five consecutive experiments, and the hydrogen production efficiency of each experiment was recorded. It can be clearly found that the high stability and hydrogen production activity are still maintained after 5 cycles.

[0160] like Figure 5 The figure shows the hydrogen production activity of the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Example 1, the self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 1, and the TiO2 precursor of Comparative Example 2. The copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Example 1 produces 35.06 mmol·g of hydrogen in the sixth hour. -1 The self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 1 produced 12.486 mmol·g of hydrogen in the sixth hour. -1 The TiO2 precursor of Comparative Example 2 produced 0.843 mmol·g hydrogen in the sixth hour. -1. The copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Example 1 has a hydrogen production capacity 2.8 times higher than that of the self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 1, indicating that the richer valence state of copper in the form of channels in the hybrid material will make the TiO2 and CuIn bimetallic porphyrin MOFs more closely compounded, and the interfacial interaction force will be stronger, providing more active sites, accelerating the separation and transfer of electron-hole pairs, and promoting the photocatalytic hydrogen evolution reaction. The copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Example 1 is 41 times higher than the TiO2 precursor of Comparative Example 2. The self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 1 is 14 times higher than the TiO2 precursor of Comparative Example 2, indicating that the spectral range of TiO2 is broadened after the composite Culn bimetallic porphyrin MOFs, and the bimetallic porphyrin has more abundant binding sites and reaction active centers, which is beneficial to the separation of electron-hole pairs and the improvement of photocatalytic reaction activity.

[0161] Figure 6 The figure shows the comparison of hydrogen production activity of the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Example 1, the copper multi-channel TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 3, and the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs (H2O) photocatalyst of Comparative Example 4. The amount of hydrogen produced by the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Example 1 in the 6th hour is 10.97 times that of the copper multi-channel TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 3, indicating that after the TiO2 precursor is calcined at 350°C, the side chain groups of TiO2 are broken, and it is no longer reducing, and the metal ions cannot be reduced to low-valent ions. The interfacial interaction force between TiO2 and CuIn bimetallic porphyrin MOFs is weakened, and the interfacial resistance is increased, resulting in the shedding of the TiO2 precursor in the photocatalytic hydrogen production reaction, and the hydrogen production activity is greatly reduced. The amount of hydrogen produced in the 6th hour of photocatalysis by the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs of Example 1 is 2.77 times that of the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs (H2O) photocatalyst of Example 4, indicating that when water is used as the reaction solvent, the CuIn bimetallic porphyrin MOFs cannot be well dissolved in water, and the interface contact with the TiO2 nanoparticles is insufficient, resulting in rapid recombination of photogenerated electron-hole pairs, which is not conducive to the photocatalytic hydrogen production reaction.

[0162] Figure 7The figure shows the hydrogen production activity comparison of the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Example 1 and the fixed copper site TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst of Comparative Example 5. The hydrogen production rate of the copper multi-channel self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst in the sixth hour is 35.06mmol·g -1 The fixed copper site TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst produced hydrogen at a rate of 23.17 mmol·g in the sixth hour. -1 , indicating that after copper is fixed on the TiO2 precursor, it is impossible to construct a channel between the TiO2 precursor and the CuIn bimetallic porphyrin MOFs, thereby failing to provide more active sites, and the efficiency of separation and transfer of electron-hole pairs is reduced, which is not conducive to promoting the photocatalytic hydrogen evolution reaction.

[0163] Figure 8 The figure shows the comparison of the hydrogen production activity of a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst in Comparative Example 1 and a self-reducing TiO2 / CuAl bimetallic porphyrin MOFs photocatalyst in Comparative Example 6. The effect of the metals around the porphyrin MOFs on the photocatalytic activity under the same main group was explored. The hydrogen production activity of the self-reducing TiO2 / CuIn bimetallic porphyrin in Comparative Example 1 is better than that of the self-reducing TiO2 / CuAl bimetallic porphyrin in Comparative Example 6. Although In and Al are both elements of the third main group and have similar reaction activities with porphyrin copper, relative to Al 3+ ,In 3+ It has strong oxidizing properties and can easily obtain electrons during the reaction. Therefore, compared with TiO2 / CuAl bimetallic porphyrin MOFs, it can capture electrons more effectively, promote charge separation and transfer, and thus help improve photocatalytic activity.

[0164] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels, characterized in that: The first copper salt, the TiO2 precursor, and the CuIn bimetallic porphyrin MOFs are mixed in a first organic solvent, and a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels is obtained by solvothermal reaction, and the reaction is completed.

2. The method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connection according to claim 1, characterized in that: The mass ratio of the first copper salt, the TiO2 precursor, and the CuIn bimetallic porphyrin MOFs is 0.5-16:100:4; The mass volume ratio of the TiO2 precursor to the first organic solvent is 50:3-5 mg / mL.

3. The method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connection according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 100-140°C.

4. The method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connection according to claim 1, characterized in that: The first copper salt is CuCl2; The first organic solvent is DMF.

5. The method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connection according to claim 1, characterized in that: The preparation process of the TiO2 precursor is as follows: tetrabutyl titanate, a hydrolysis inhibitor, water and nitric acid are mixed, and the mixture is heated, stirred, dried and ground to obtain the TiO2 precursor.

6. The method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connection according to claim 5, characterized in that: The volume ratio of tetrabutyl titanate, hydrolysis inhibitor, water and nitric acid is 5-15:5-10:100-200:1; The hydrolysis inhibitor includes one or more of ethanol, acetone, and acetylacetone; The heating and stirring temperature is 40 to 80°C; The drying temperature is 120-180°C.

7. The method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connection according to claim 1, characterized in that: The preparation process of the CuIn bimetallic porphyrin MOFs is as follows: TCPP, benzoic acid, a second copper salt, and an indium salt are mixed in a second organic solvent, heated to reflux, cooled, centrifuged, and dried to obtain the CuIn bimetallic porphyrin MOFs.

8. The method for preparing a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connection according to claim 7, characterized in that: The mass ratio of TCPP, benzoic acid, the second copper salt and the indium salt is 2-8:1-5:5-15:10; The second copper salt is CuCl2; The indium salt is In(NO3)3; The second organic solvent is DMF; The mass volume ratio of the TCPP to the second organic solvent is 20-80:100 mg / mL; The heating reflux temperature is 120-180°C; The drying temperature is 40-80°C.

9. A self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst connected by copper multi-channels, which is prepared by the preparation method described in any one of claims 1 to 8.

10. The use of a self-reducing TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst with copper multi-channel connection as claimed in claim 9 in the field of photocatalysis, characterized in that: The copper multi-channel connected self-reduced TiO2 / CuIn bimetallic porphyrin MOFs photocatalyst is used as a photocatalyst for hydrolysis to produce hydrogen.

Citation Information

Patent Citations

  • Method for preparing SNP-TiO2-coated Cu-MOF composite material photocatalyst and application of SNP-TiO2-coated Cu-MOF composite material photocatalyst

    CN115090330A

  • Lithium strontium titanate / titanium dioxide heterojunction photocatalyst as well as preparation method and application thereof

    CN115487799A

  • Copper modified titanium dioxide photocatalyst with hierarchical pore structure and preparation method of copper modified titanium dioxide photocatalyst

    CN118403632A